Structure and orientation of halorhodopsin in the membrane: a proteolytic fragmentation study. - Schobert, B (1988)
Halorhodopsin (HR), the light-driven chloride pump in halobacteria, was digested with various proteolytic enzymes. As expected, carboxypeptidase A removed 14 amino acids from the C-terminal tail of detergent-solubilized HR, producing a fragment of 25.2 kd in size. Membrane-associated HR could be digested as well, but not in right-side-out sealed cell envelope vesicles. We conclude, therefore, that the orientation of HR in the cytoplasmic membrane is such that the C-terminal tail faces the cytoplasmic side. Tryptic digestion of detergent-solubilized HR resulted in the removal of the same C-terminal segment, but also in the production of two more cleavage products (molecular masses of 20.9 and 16.8 kd respectively). These cleavage sites were determined by amino acid sequencing of the newly produced N termini, and they turned out to be within interhelical loops in an earlier proposed structural model for HR. Incubation with chymotrypsin and thermolysin yielded different sites of cleavage, but also in regions which were proposed to be accessible on the surface of the protein. Since the results show that three of six proposed interhelical loop segments contain proteolytic digestion sites, they support the proposed structural model for HR.